Gypsum improves broiler litter quality and reduces footpad lesions - Galli G.M.* (2021)
© 2021 CSIRO.Context: To optimise litter quality, the use of gypsum (CaSO4·2H2O) may be a good strategy. Brazil is the largest exporter of chicken meat in the world. The Asian market, in particular, demands chicken feet; however, quality standards for export demand that the feet have to be free (or almost free) of injuries. It is therefore essential to reduce the incidence of footpad lesions. Aims: To determine whether the replacement of lime (Ca(OH)2) by gypsum in poultry broiler litter improves litter quality, pododermatitis scores, animal performance and health. Methods: In total, 320, 1-day-old male Cobb 500 broilers were divided into the following four groups: control group in which no gypsum or lime were added to the litter (TC); group with 0.5 kg of lime/m2 of litter (TL 0.5); group with 0.5 kg of gypsum/m2 of litter (TG 0.5); and group with 1.0 kg of gypsum/m2 of litter (TG 1.0). The pH, dry matter, water activity and surface temperature of the litter were measured on Days 21, 35 and 42. Animal performance parameters were measured on Days 1, 21, 35 and 42; blood collection was performed on Day 42 for biochemical and haematological analysis, in addition to excreta samples and litter for bacterial counts. At the end of the experiment, 32 broilers were humanely killed for tissue analysis (liver and intestine) and histopathology. The degrees of footpad injury (Day 42) were graded using a 5-point scale, from 0 (no injury), to 1, 2, 3 and 4 (severe injury). Key results: No differences were found between treatments regarding performance (P > 0.05). With respect to intestinal parameters, there were significant differences in villus height and crypt depth, with TL 0.5, and TG 1.0 showing larger villi than did the control group. The shallowest crypt depths were seen in TC and TG 0.5. Litter dry matter content was significantly higher than in the control (TC) at Day 35 in TG 0.5, and at Day 42 in the TG 1.0 treatments. The litter temperature was significantly higher in the TL 0.5 treatment than in the TG 1.0 at 21 days, but they were not different from that in the control. At Day 35, both TG treatments had significantly lower litter temperature than did the control group, but no differences were observed at Day 42. The treatments had no effect on haematology or biochemical properties, nor on litter or bacterial counts in excreta. Broilers raised on litter treated with gypsum showed 50% fewer Grade 3 and 4 footpad lesions than did the control animals on Day 42, an important finding mainly for lesion grades between 3 and 4 that could prevent export of feet. Conclusions: Gypsum at 0.5 kg/m2 showed the best results regarding litter quality, reducing the incidence of footpad lesions without compromising animal health or performance. Implications: Applying gypsum to litter at 0.5 kg/m2 reduces the number of broilers with pododermatitis, an economic benefit to the poultry industry.